Diverse policies leading to contrasting impacts on land cover and ecosystem services in Northeast China. (10th December 2019) - Mao, Dehua; He, Xingyuan; Wang, Zongming; Tian, Yanlin; Xiang, Hengxing; Yu, Hao; Man, Weidong; Jia, Mingming; Ren, Chunying; Zheng, Haifeng
Abstract: Understanding where important ecosystem services originate in space and how they change in time is essential for sustainable ecosystem management. Spatially explicit information of integrated changes in land cover and ecosystem services impacted by diverse policies has been unavailable in Northeast China, limiting the improvement of human well-being. Therefore, this study integrated remote sensing, meteorological records, and statistical data to evaluate the impacts of policies on land cover and ecosystem services from 2000 to 2015. The results reveal that diverse policies induced both notable changes in land cover, as well as geospatially varied changes in ecosystem services. Specifically, agricultural cultivation was still the dominant factor driving the losses of woodland, grassland, and wetland, while large areas of croplands have been returned to natural land cover, including a net area increase in woodland (2256 km 2 ). Cropland expansion occurred at the expense of wetland (7121 km 2 ), while the expansion of built-up land was converted primarily from cropland (62.8%). Marked decrease in water yield was observed, while sandstorm prevention, habitat suitability, and grain production have been enhanced on the scale of Northeast China. Moreover, soil retention and ecosystem carbon stock decreased slightly. In terms of present policies and changes in ecosystem services, it is important to rethink the emphasis on food production, reduce policy-driven natural ecosystem losses, and enhance the effectiveness of ecological projects. The findings are expected to help achieve win-win outcomes between ecological conservation and social-economic development in Northeast China.